Screening technology of cyclic peptide library based on gene encoding - Yangqiang Chen; Chonggang Duan; Kai Chen; Shumeng Sun; Daizhou Zhang; Xiangjing Meng (Elsevier, 2022)
As a powerful tool for the discovery of peptide compounds, high-throughput library screening technology can also perform multitarget screening with high chemical diversity as a condition, which accelerates the process of exploring high-affinity peptide molecules. These techniques can be generally divided into in vitro and in vivo screening techniques, both of which play important roles in peptide drug discovery. Compared with linear peptides, cyclic peptides have been proven to have good bioavailability, membrane permeability, and stability and longer half-lives and have gradually become a topic of high interest in peptide drug research. High-throughput library screening technology plays an important role in the development of cyclic peptide drugs. Based on published studies, this paper reviews the high-throughput library screening technology used in the development of cyclic peptide drugs.